Examining Validity and Reliability of General English Course Assessments in Higher Education - Abila Meika Kurnia Putri; Barlian Kristanto; Muhammad Soali (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study investigated the validity and reliability of a General English Course assessment tool at Universitas Harapan Bangsa. Using a quantitative descriptive technique, the study examined the assessment items using point-biserial correlation for validity and Cronbach's alpha for reliability. While the instrument had high overall reliability, several items needed to be revised to improve its validity. The findings indicate that the assessment instrument is generally reliable and valid; nevertheless, continuing monitoring and adjustment are required to maintain its quality and assure accurate evaluation of student English competence.